Refiguring Schools in an Age of Inclusivity: Creating Compassionate Classrooms in South African Schools: Refiguring Schools in an Age of Inclusivity: Creating Compassionate Classrooms in South African Schools - Agyeman, Nana Yaw Brenya; Aphane, Vanessa (International Journal of Educational Innovation and Research, 2025)
This study examines the need for teachers to use compassionate methods to create inclusive classrooms that address the diverse needs of students, considering South Africa's apartheid history. The research question is: How can South African schools be reconfigured to create inclusive and compassionate learning environments that meet the diverse needs of all learners, particularly those from underprivileged backgrounds? The study adopted a qualitative approach and a case study design to explore and gain an in-depth understanding of its objectives. Six teachers were purposely selected for interviews, and forty-six students participated in focus group discussions. Semi-structured interviews and focus group discussions served as the data collection methods, while thematic analysis was employed to identify the patterns and themes that emerged from the data. From the interviews, teachers emphasised the importance of compassion and empathy in meeting students' diverse needs, particularly those from disadvantaged backgrounds. Classroom observations revealed limited student engagement and reliance on teacher-centred pedagogies, hindering active participation and failing to address diverse learning preferences. These findings suggest a disconnect between teachers' expressed values of compassion and empathy and the observed classroom practices, which rely heavily on traditional, teacher-centred methods that may not effectively engage diverse learners. This disconnect shows the need for professional development and support to implement inclusive education strategies to address the needs of students. This study highlights a gap between teachers' perceived value of compassion and empathy and their classroom practices, emphasising the need for professional development in inclusive education strategies.